Propolis green biofilm for the immobilization of carbon nanotubes and metallic ions: Development of redox catalysts - Roberto de Oliveira, Paulo (2021)
Greener materials have been used in the construction of electrochemical devices, becoming one of the main strands of this scientific development area. Thin films based on natural and renewable sources, such as propolis, allow the development of biocomposites. Hence, we have proposed the use of a thin film based on propolis for the stable and homogeneous immobilization of carbon nanotubes (CNTs), which increased the electrical conductivity of the base electrode (glassy carbon electrode) by almost 500 thousand times. The CNTs/propolis biofilm proportion was optimized by multivariate analysis, providing a decrease in the number of experiments, the demand for reagents, and analysis time. The biocomposite thin film was used for the spontaneous preconcentration and anchoring of metal ions, and the electrochemical synthesis of redox mediators and catalysts. This qualifies the proposed strategies for the development of eco-friendly electrochemical devices.